Testing the Inverted-U Theory of the Stress-performance Relationship in Four BPO Companies in Metro Manila - Adan, Joyce N. (Philippine Journal of Labor and Industrial Relations, 2021)
The purpose of this study has been to identify the relationship between stress and work performance among the business process outsourcing (BPO) call center employees in the Philippines, with particular focus on testing the inverted-U theory relation. Two different stress scales were used across all four BPO companies in order to make a comparative analysis of the stress-performance relationship. The first stress scale aims to measure objective stress, which primarily refers to job-specific stress, while the second stress scale is meant to gauge general stress, which involves both work stress and stress outside of work (i.e., personal). While there is such variation between the two scales, they both measure psychological stress. Findings reveal a positive linear relationship between lower levels of objective stress and work performance, while a U-shaped curve has been found to exist between general stress and work performance and among identified specific groups such as males, non-college graduates, single employees, and night shift workers. The inverted-U stress-performance relation was only found to exist among companies with stronger wellness programs,